THE ROLE OF BLOCKCHAIN TO SOLVE PROBLEMS OF DIGITAL RIGHT MANAGEMENT (DRM) - Jehan Afwazi Ahmad; Teduh Dirgahayu (Jurnal Teknik Informatika (Jutif), 2023)
In recent years, internet user was grown significantly. Even though many problems arise due to internet abuse. The sectors affected by the internet is digital assets or digital right. Various ways are done to solve the violation. One of that ways is to develop digital protection or Digital Right Management (DRM). However, the DRM technology has several disadvantages such as there is no way to track the leak and prove a copyright violation, the user is unable to authenticate the content since the content source is unknown, there is no user restriction to download the content, the system isn’t provided the feature to alienate ore transfer ownership the content to other, and the system using centralize model that requires many issues, especially trust issue. Fortunately, the blockchain is a decentralized, secure, reliable, immutable, and tamper-proof paradigm. The blockchain is also built upon public key cryptography and has a smart contract that can solve or complement DRM problems. This paper discusses how the blockchain solves DRM problems. The results show that blockchain solves DRM problems. A narrative literature review was conducted with several stages, including a source search of papers, articles and news articles on digital rights management and blockchain in the last five years. The next step is to identify keywords related to the topic, to review the sources, and to compile the paper.